Perancangan Sistem Informasi Pengelola Barang/Inventaris Di Jc Komp - Rizki Hidayat, Achmad (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
Inventory information system is a system used to enter inventory data into the database, so that there are no errors in input, output data, and reporting based on the desired data. based on surveys and interviews with jc comp personnel, information was obtained that the existing system in the jc comp warehouse section is still manual. therefore, the system that will be created by the author is the result of a replication of the existing system in the jc comp warehouse section. in addition to the process of input and output of goods, this information system is also equipped with features for creating data reports, input and output of goods, and searching for goods data by item name. with the inventory information system is expected to be useful for the warehouse parts jc comp. By implementing this system in the jc comp warehouse, it is hoped that it can reduce errors that may occur. this system is also expected to further speed up the process of input, output, and report generation, which in turn will help the jc comp warehouse